Epistemological reading of collage art and its preoccupations in the education of artistic expression (Journal of the College of Basic Education, 2023)
Summary of the research:Contemporary epistemology has contributed to the development of scientific thought, which contributes to the establishment of relationships between the components of the artistic achievement to give aesthetic organizations in the diversity of metaphors of ideas, and we do not find that collage art has a role in changing the concepts of beauty that fused with it by relying on a knowledge structure, according to which its capabilities are formed with the elements of its structure according to The surface of the artwork is formed in which the artistic images are the objective and expressive equivalent in a way that is reproduced by the individual artist and presented again in an aesthetic way, so the person creates forms with stages of expression to the implementation of creative forms. Through the forms of raw materials and performance techniques used, this research included the definition of the terms contained, and the second chapter contained two chapters on me, the first on epistemology and art, and the second on collage art and its role in artistic expression. As for the fourth chapter, I am concerned with the results, and among them, the artwork is a field of signs with different indications, revealing the structural structure in contemporary collage art that stimulates the aesthetic taste of the learner in terms of the relationships between the structures of the artwork as in Model 1, 2, 3, conclusions, recommendations, proposals, and an English summary.Keywords: epistemology, art, education